A fluorescent hormone biosensor reveals the dynamics of jasmonate signalling in plants - Larrieu, Antoine; Champion, Antony; Legrand, Jonathan; Lavenus, Julien; Mast, David; Brunoud, Geraldine; Oh, Jaesung; Guyomarc’h, Soazig; Pizot, Maxime; Farmer, Edward E.; Turnbull, Colin; Vernoux, Teva; et al. (Nature Publishing Group, 2015)
Activated forms of jasmonic acid (JA) are central signals coordinating plant responses to stresses, yet tools to analyse their spatial and temporal distribution are lacking. Here we describe a JA perception biosensor termed Jas9-VENUS that allows the quantification of dynamic changes in JA distribution in response to stress with high spatiotemporal sensitivity. We show that Jas9-VENUS abundance is dependent on bioactive JA isoforms, the COI1 co-receptor, a functional Jas motif and proteasome activity. We demonstrate the utility of Jas9-VENUS to analyse responses to JA in planta at a cellular scale, both quantitatively and dynamically. This included using Jas9-VENUS to determine the cotyledon-to-root JA signal velocities on wounding, revealing two distinct phases of JA activity in the root. Our results demonstrate the value of developing quantitative sensors such as Jas9-VENUS to provide high-resolution spatiotemporal data about hormone distribution in response to plant abiotic and biotic stresses.